PURE: CV Drugs Underused for Secondary Prevention in Poor and Rural Populations - Jacobson, Anne (MD Conference Express, 2011)
Despite proven efficacy and relatively low cost, key secondary prevention medications are widely underused in populations with prevalent cardiovascular disease particularly in poor countries and rural areas, according to findings from the Prospective Urban Rural Epidemiological [PURE] study.